An immunochemical evaluation of chicken egg yolk antibodies (IgY) and their preliminary physico-chemical characterization - Epstein, Heather(Heather Barbara) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1987.